2017
DOI: 10.1371/journal.pone.0183095
|View full text |Cite
|
Sign up to set email alerts
|

Translation, cultural adaptation and validation of simplified Chinese version of the anterior cruciate ligament return to sport after injury (ACL-RSI) scale

Abstract: PurposeTo translate and cross-culturally adapt the anterior cruciate ligament-return to sport after injury (ACL-RSI) into simplified Chinese [ACL-RSI (Cn)].MethodIn this diagnostic study, the translation, cross-culturally adaptation, and validation of the ACL-RSI was performed according to international guidelines. A total of 112 patients with ACL reconstruction participated in this study. All were capable of competitive sports before the injury and completed the Knee Injury and Osteoarthritis Outcome (KOOS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 48 publications
14
11
1
Order By: Relevance
“…Internal consistentcy of the ACL-RSI-Lt, according to Cronbach alpha index, was 0.94 which is considered as excellent. Compared to the findings of our study, the Dutch [10] and Swedish [15] versions had the same Cronbach alpha (0.94), the Chinese [12] and French [14] versions had 0.96, the Turkish [11] version had 0.88 and the Brazilian [13] version had 0.87. All studies consolidate the strong correliation between the 12 questions of the scale, demonstraiting that 3 subscales (emotions, confidence in the performance and risk assessment) cannot be used separately.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Internal consistentcy of the ACL-RSI-Lt, according to Cronbach alpha index, was 0.94 which is considered as excellent. Compared to the findings of our study, the Dutch [10] and Swedish [15] versions had the same Cronbach alpha (0.94), the Chinese [12] and French [14] versions had 0.96, the Turkish [11] version had 0.88 and the Brazilian [13] version had 0.87. All studies consolidate the strong correliation between the 12 questions of the scale, demonstraiting that 3 subscales (emotions, confidence in the performance and risk assessment) cannot be used separately.…”
Section: Discussioncontrasting
confidence: 67%
“…In the Dutch version correlation between ACL-RSI and IKDC was 0.51 [10], in the Brazilian version was 0.58 [13], while in the Turkish version was 0.44 [11] and in the French version the correlation was 0.42 [14]. Chen et al [12] reported a week correlation between ACL-RSI and IKDC subscales. In our study, only the correlation between ACL-RSI-Lt and subscale IKDC-sports was week.…”
Section: Discussionmentioning
confidence: 99%
“…The instrument that we chose to measure the patient’s subjective outcome was the IKDC subjective knee score, which is a well-validated knee scale that records the patient’s self-reported knee symptoms and function 18 and which showed a moderate univariate correlation with ACL-RSI scores in validation studies. 7,9,17 Note that this measure was more strongly associated with psychological readiness than the measure of physical function (hop-test limb symmetry) and that knee laxity had no association with psychological readiness. Therefore, patient self-reported outcomes have a strong association with psychological readiness to RTS.…”
Section: Discussionmentioning
confidence: 96%
“…Webster, Feller, and Lambros (2008) developed and studied the validity of the ACL Return to Sports after Injury (ACL-RSI) scale, which was designed to evaluate three psychological responses of athletes in relation to sport resumption following ACL injury and/or surgery: emotions, confidence in performance, and risk appraisal. The ACL-RSI has been translated into several languages and is considered valid and reliable (Bohu, Klouche, Lefevre, Webster, & Herman, 2015;Chen et al, 2017;Harput et al, 2017;Kvist et al, 2013;Silva, Mendes, Lima, & Almeida, 2017;Slagers, Reininga, & van Den Akker-Scheek, 2017). Glazer developed the Injury Psychological Readiness to Return to Sport (I-PRRS) scale to assess the psychological readiness of injured athletes to return to sports participation, irrespectively of the type of injury (Glazer, 2009).…”
Section: Introductionmentioning
confidence: 99%